EVALUATION OF PRESERVATION PROBLEMS OF THE HISTORICAL GARDENS AND THEIR ARCHITECTURAL ELEMENTS CONSIDERING THE PALACES AND PAVILIONS IN ISTANBUL - Uguryol, Drahsan (MIDDLE EAST TECHNICAL UNIV, 2020)
The historical gardens in Istanbul vary according to their purpose of use, design features, constructions they are associated with, and constitute an important part of Istanbul's cultural heritage. Among these gardens, the palace and pavilion gardens are the most special and decorated gardens with their design features, plant varieties, and architectural elements. This is due to the fact that care is taken for these gardens since palaces and pavilions are imperial structures and because of the personal interest of the sultans in the gardens and their arrangement by the domestic and foreign gardeners as well. However, the historical gardens of Istanbul have been damaged due to the negative effects of urbanization, improper interventions, problems arising from use, negligence, and material deterioration. The aim of this study was to examine the effects of negative factors on the preservation of historical gardens in Istanbul on the palace and pavilion gardens. In line with this aim, samples from palace and pavilion gardens were selected, the extent of preservation of these gardens was determined by carrying out a field study and archival research, and the effects of the preservation problems on the selected gardens were shown by listing them in a table. The research revealed that these preservation problems also had negative effects on the gardens of palaces and pavilions. The results were presented under the relevant headings. When the study was evaluated, it was understood that despite all these negative issues, the palace and pavilion gardens have survived to a certain extent with their landscape arrangements, plant varieties and architectural elements and still reflect the Ottoman garden culture. These areas, which are the indicators of garden aesthetics and design principles of the period they were designed and also influenced by the cultures of other states with which the Ottoman Empire was in political relations, constitute an important part of Istanbul's historical cultural landscape and heritage. Therefore, in the conclusion part of the study, suggestions based on the research were made for the preservation and restoration works that should be done in order to ensure the continuity of palace and pavilion gardens, to preserve their cultural and aesthetic value, and to transfer them to future generations in a way to form a whole with the structures they contain.
Keywords: Historical gardens; palace gardens; pavilion gardens; national palaces; preservation problems; Architecture